Evaluating six soft approaches - Lene Sørensen; René Victor Valqui Vidal (Colegio de Economistas de A Coru\~na, 2008)
The paper introduces and evaluates six soft approaches used in strategy development and planning. We take a planner's perspective on discussing the concepts of strategy development and planning. This means that we see strategy development and planning as learning processes based on Ackoff's interactive planning principles to be supported by soft approaches in carrying out the principles in action. These six soft approaches are suitable for supporting various steps of the strategy development and planning process. These are the SWOT analysis, the Future Workshop, the Scenario methodology, Strategic Option Development and Analysis, Strategic Choice Approach and Soft Systems Methodology. Evaluations of each methodology are carried out using a conceptual framework in which the organisation, the result, the process and the technology of the specific approach are taken into consideration. Using such a conceptual framework for evaluations of soft approaches increases the understanding of them, their transparency, and their usability in practice.
Keywords: 330; strategic planning; soft OR